Budaya Lokal Sebagai Kurikulum Muatan Lokal dalam Pendidikan Agama Islam - Rofiq (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2019)
Local content is one of the elements in the Education Unit Level Curriculum Structure. Local content is prepared by taking into account the socio-cultural conditions of the local community. In the Yogyakarta setting, one form of local content is Javanese culture. In Javanese culture, it can be seen a lot of symbolic actions both in traditions (habits), religion (religion), and art (beauty) which can be used as a medium to explore noble values ​​that can be transformed to students. In practice, an integrated and ecological approach is used. The integrative approach is carried out in a way that local content is integrated or carried out together with other subjects. While the ecological approach is intended as learning material for local content directly using the natural environment and local social culture. Examples of the two approaches manifest in the integration of the First Grebeg Mulud celebration as a socio-cultural environment with the subjects of Islamic Cultural History.